210 An Audit to Evaluate Abdominal XR Requests in Surgical Patients. (28th February 2022) - Bryce, A.; Al-Azzawi, M.; Watt, D.
Abstract: Abdominal x-rays (AXR) are a useful tool in investigating a number of pathologies. However, they expose the patient to up to 7 times more radiation than a standard chest x-ray 1 . AXR's that are requested without appropriate indication are not an efficient use of resources. Our aim was to evaluate if requests for AXR's being made are in line with Royal College of Radiologists (RCR) iRefer guidelines 2 and try improving their adherence. Three data cycles of AXR requests made by surgical staff at Crosshouse hospital were gathered – between January & February, April, and July. Clinical history of the patients and indications in the request for the AXR were compared with guideline recommendations. In total 52 requests for AXR's were made during January-February, of which 32 (62%) were made appropriately and 20 (38%) did not match guidelines, as the patient's presenting complaint and clinical history did not match one of the recommended indications to perform AXR. After circulation of educational posters, 70% of requests were made in line with guidelines in April. Followed by 77% in July after a departmental presentation on the use of AXR. AXR's requested during these time periods were not all made in line with guidelines. The most commonly noted error was the AXR being requested to rule out obstruction when the clinical history wasn't suspicious of obstruction. This QI project has demonstrated sustainable change and increased the adherence of AXR requests with RCR guidelines within the department.